2011
DOI: 10.1155/2011/136802
|View full text |Cite
|
Sign up to set email alerts
|

Band 3 Missense Mutations and Stomatocytosis: Insight into the Molecular Mechanism Responsible for Monovalent Cation Leak

Abstract: Missense mutations in the erythroid band 3 protein (Anion Exchanger 1) have been associated with hereditary stomatocytosis. Features of cation leaky red cells combined with functional expression of the mutated protein led to the conclusion that the AE1 point mutations were responsible for Na+ and K+ leak through a conductive mechanism. A molecular mechanism explaining mutated AE1-linked stomatocytosis involves changes in AE1 transport properties that become leaky to Na+ and K+. However, another explanation sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 68 publications
(89 reference statements)
6
21
0
Order By: Relevance
“…We could observe by stopped-flow spectrofluorometry a rapid intracellular alkalinization corresponding specifically to this exchange in HEK293 expressing WT AE1, whereas no activity was detectable in parental cells. Our results also showed that E758K mutant was fully active, as previously reported in Xenopus oocytes (4,29). Indeed, although the alkalinization rate constant was five to six times lower for E758K mutant than for WT AE1 (0.07 vs. 0.38 s Ϫ1 ), normalization of transport values with surface expression level indicated comparable relative activities (98 vs. 100%) and apparent unit permeabilities (11.96 ϫ 10 Ϫ3 vs. 9.81 ϫ 10 Ϫ3 m 3 /s) of both E758K mutant and normal proteins.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…We could observe by stopped-flow spectrofluorometry a rapid intracellular alkalinization corresponding specifically to this exchange in HEK293 expressing WT AE1, whereas no activity was detectable in parental cells. Our results also showed that E758K mutant was fully active, as previously reported in Xenopus oocytes (4,29). Indeed, although the alkalinization rate constant was five to six times lower for E758K mutant than for WT AE1 (0.07 vs. 0.38 s Ϫ1 ), normalization of transport values with surface expression level indicated comparable relative activities (98 vs. 100%) and apparent unit permeabilities (11.96 ϫ 10 Ϫ3 vs. 9.81 ϫ 10 Ϫ3 m 3 /s) of both E758K mutant and normal proteins.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, although the alkalinization rate constant was five to six times lower for E758K mutant than for WT AE1 (0.07 vs. 0.38 s Ϫ1 ), normalization of transport values with surface expression level indicated comparable relative activities (98 vs. 100%) and apparent unit permeabilities (11.96 ϫ 10 Ϫ3 vs. 9.81 ϫ 10 Ϫ3 m 3 /s) of both E758K mutant and normal proteins. The defect in Cl Ϫ /HCO 3 Ϫ transport activity of G796R and R730C mutants was not due to reduced expression or processing of the proteins to the cell surface and also corroborates their inactivity reported in Xenopus oocytes (4,15,28). The inducible system used is a valuable tool to control AE1 expression in HEK293 cells, and the heterogeneous amounts of the protein at cell surface from one sample to the other actually validated our method based on the comparison of activities.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations